2015
DOI: 10.4274/tjo.99267
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum and Treatment Approaches in Corneal Burns

Abstract: Objectives:To evaluate the clinical findings, treatment modalities and long-term prognosis of chemical and thermal burns of the cornea.Materials and Methods:Twenty-one patients (27 eyes) who were followed at two centers for corneal chemical and thermal burns between 2001 and 2013 were included. Eyes were grouped into four grades according to the severity of burn using Roper-Hall classification. Age, gender, type of burn, follow-up duration, corrected visual acuity before and after treatment, treatment modaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…However, surgical treatment is required in patients with high-grade LSCD cases. 19,33 In the present study, almost half the eyes developed LSCD, and one third of these eyes required LSCT. The relationship between injury grade and LSCD was statistically significant ( P <0.001).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…However, surgical treatment is required in patients with high-grade LSCD cases. 19,33 In the present study, almost half the eyes developed LSCD, and one third of these eyes required LSCT. The relationship between injury grade and LSCD was statistically significant ( P <0.001).…”
Section: Discussionsupporting
confidence: 46%
“…15 In brief, according to the effect mechanisms of the causative agents, high-grade burns mostly occur with alkaline agents. Muftuoglu et al 19 reported that 48.1% of alkali burn patients were high-grade (grade 4–6). 19 Nevertheless, in the present study, no statistically significant relationship between injury grade and agent type was demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“… 52 , 65 Acid injuries typically cause protein coagulation and precipitation in the epithelium, forming a barrier that further limits penetration of the burning agent deeper into the eye. 66 , 67 Corneal injuries caused by thermal agents (e.g., resulting from exposure to scalding liquids, direct flame, or burning items) 68 and radiation exposure (e.g., UV light) 69 tend to be rarer and less severe. However, and similar to chemical injuries, thermal and radiation damage to the cornea can result in further stiffening at later stages due to tissue contracture and fibrosis.…”
Section: Corneal Biomechanics In Health and Diseasementioning
confidence: 99%
“…The type of chemical involved and the exposure time are the most important information to start treatment. The ischemia in the limbal area may give a clue about the severity and the extent of the injury as well as the estimated visual function [16]. Alkalis can cause irreversible damage to the eye, in between 5 and 15 minutes, and many are considered the most common cause of ocular chemical burns [16][17][18].…”
Section: Chemical and Thermal Injuries Of The Eyementioning
confidence: 99%
“…The ischemia in the limbal area may give a clue about the severity and the extent of the injury as well as the estimated visual function [16]. Alkalis can cause irreversible damage to the eye, in between 5 and 15 minutes, and many are considered the most common cause of ocular chemical burns [16][17][18]. The assessment of severity involves three factors-damage to the lids and adnexes, degree of limbal ischemia, and the degree of acute corneal stromal opacification [19].…”
Section: Chemical and Thermal Injuries Of The Eyementioning
confidence: 99%